Long-term effects of early childhood malaria exposure on education and health: Evidence from colonial Taiwan - Simon Chang; Belton M. Fleisher; Seonghoon Kim; Shi-yung Liu (Institute for the Study of Labor (IZA), 2011)
We estimate the effects of early childhood malaria exposure on education and health at older ages by exploiting variations in malaria exposure risk around birth that resulted from a universal malaria eradication campaign in colonial Taiwan in the early 20th century. We find that malaria exposure around birth leads to lower life-time educational attainment and to worse mental and physical health outcomes in old age as reflected in particular in worse cognitive function, a higher likelihood of cardiovascular diseases and a higher mortality hazard, compared to those who were not exposed.
urn:nbn:de:101:1-201104114009
Keywords: I12; I18; I21; O15; O18; 330; malaria; early childhood; education; health; Taiwan; Tropenkrankheit; Kinder; Bildungsniveau; Erwachsene; Gesundheit; Taiwan